PENGARUH PENGENDALIAN INTERNAL, TINDAK LANJUT TEMUAN AUDIT TERHADAP PENCEGAHAN FRAUD, KUALITAS LAPORAN KEUANGAN SEBAGAI MEDIASI : THE EFFECT OF INTERNAL CONTROL, FOLLOW-UP OF AUDIT FINDINGS ON FRAUD PREVENTION WITH THE QUALITY OF FINANCIAL REPORTS AS MEDIATION - Muslianti Middin; Antong Antong; Halim Usman (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2023)
This study examines the impact of internal control & follow-up audit findings on fraud prevention, with the quality of financial reports as mediation at the Luwu Raya Inspectorates, using quantitative methods & analyzed using a descriptive approach. The population includes all auditors at the Luwu Raya Inspectorates, the sampling technique uses a saturated sample where all members of the population are sampled, the sample in this study is all auditors at the Luwu Raya Inspectorates with 61 respondents. Data analysis using SEM-PLS (SmartPLS). The research results show that internal control, follow-up on audit findings and the quality of financial reports have a significant influence on fraud prevention. Then, internal control & the follow-up of audit findings have a significant effect on the quality of financial reports, as well as the relationship between follow-up audit findings through the quality of financial reports on fraud prevention where the quality of financial reports is able to mediate the follow-up of audit findings on fraud prevention. Meanwhile, the relationship between internal control through the quality of financial reports on fraud prevention does not have a significant effect.